The invasion law of drilling fluid along bedding fractures of shale - Li, Hong; Wang, Qing; Zhang, Kun; Zhang, Qing Hui; Song, Tao; Zhang, Chuang; Zhuo, Lu Bin; Hao, Chen; Feng, Fu Ping; Wang, He Yuan; Zhang, Yin Quan (Frontiers in Earth Science, 2023)
In the process of drilling, the drilling fluid will invade into the bedding plane of shale under the action of pressure difference that will cause hydration collapse and wellbore instability. In order to ensure the wellbore stability during shale oil and gas drilling, it is necessary to clarify the invasion law of drilling fluid along bedding fractures during the drilling process. The immersion experiment method is often used to study the invasion law of drilling fluid, which is quite different from the actual invasion process of drilling fluid underground. In this paper, the depth of drilling fluid invasion into shale under different confining pressures and displacement times is intuitively and accurately determined by the displacement experiment and NMR scanning first. Also, then the mathematical relationships between drilling fluid invasion depth and invasion time, invasion pressure difference, confining pressure, bedding angle, and drilling fluid viscosity were established. The errors between the calculated values of the drilling fluid invasion depth and the experimental values were less than 15%, and the calculation accuracy was high. In addition to the influence of invasion time, formation pressure difference and confining pressure on invasion depth were researched through the method of numerical simulation. The results showed that the liquid invasion depth increased logarithmically with the increase of invasion time and formation pressure difference, but it grew slowly in the later period and tended to be stable; the invasion depth decreased exponentially with the increase of confining pressure, bedding plane angle, and drilling fluid viscosity. The results in the paper provide a basis for the subsequent determination of the collapse pressure and collapse period of bedding shale.